P67 Audit of mycoplasma genitalium management: challenges in a London clinic. (16th June 2022) - Howard, Harriet; Parish, Tina; Chung, Emily
Abstract : Introduction: Mycoplasma genitalium (MG) is a sexually transmitted bacterium that infects the genitourinary tract; it is only tested if clinically indicated and not available universally in sexual health clinics. We examined the management of MG in a London sexual health clinic compared to BASHH guidelines. Methodology: Data from electronic patient records on 70 patients diagnosed with MG from May-August 2021 was analysed using Microsoft Excel. Data collected: sex, age, test indication, 'in house' and reference laboratory results, resistance profile, treatment details, test of cure (TOC) details. Results: 64.3% of positive tests were sent as per guidelines, with 35.7% inappropriate tests (see figure for indications). 10% of cases had a discrepancy between the in house and reference lab result (in house positive, reference lab negative). 50% had antibiotic resistance. 91.4% of patients were treated. 87.5% of these received appropriate treatment according to resistance profiles. 54.3% of all patients had a TOC after 5 weeks, of which 93.3% were negative; 3.3% (1) was positive and 3.3% (1) was equivocal. Discussion: The majority of patients with MG were managed as per guidelines. Some were inappropriately tested. Antibiotic resistance was slightly less prevalent than most recent national estimates (estimated national macrolide resistance 69%) (1). Most received appropriate treatment and almost all TOCs were negative. However, almost half did not have a TOC; this may be due to the pandemic but requires further review. In 10% of patients there were discrepancies between the in house and reference lab results. This identified variability in subsequent management and requires further investigation. Reference: Public Health England. Mycoplasma genitalium resistance surveillance, second pilot report. GOV-9299. [Internet]. 2021. [cited 2022 March 14]. Available from: https://assets.publishing.service.gov.uk/government/uploads/system/uploads/attachment_data/file/1011028/MARS_pilot_report_2021.pdf